Comparative Study of Mechanical Properties of Chemically Treated and Untreated Cyrtostachys Renda Fibers - Tamil Moli Loganathan; Mohamed Thariq Hameed Sultan; Qumrul Ahsan; Mohammad Jawaid; Ain Umaira Md Shah (Journal of Natural Fibers, 2022)
This study aims to investigate the effect of sodium hydroxide (NaOH) treatment on the strength and stiffness of Cyrtostachys renda (CR) leaf stalk fibers, which could potentially serve as reinforcement for polymer composites. Chemical treatment was performed with NaOH concentrations of 1, 3, and 5 wt% at a soaking time of 1 and 2 hours. The tensile strength, interfacial shear strength (IFSS) and the surface morphology of the fibers were investigated. Based on statistical analysis, the concentration of NaOH significantly affected the tensile strength, while both the concentration of NaOH and treatment duration influenced the IFSS. Increases of 130% in tensile strength and of 423% in interfacial shear strength for the fiber treated at NaOH concentration of 3% at 1 hour soaking time were found, as well as an increased crystallinity index by 12% compared to untreated CR fiber. SEM analysis revealed that shrinkage of hollow structure by the NaOH treatment occurred and subsequently fiber get denser. It can be concluded that fiber treatment with 3% NaOH for 1 hour soaking time is ideal to enhance the fiber properties. Therefore, alkali (NaOH) treated CR fiber could be a potential candidate as reinforcement in polymer composite for structural and automotive components.